Gender differences in the association of non-alcoholic fatty liver disease and metabolic syndrome with erosive oesophagitis: a cross-sectional study in a Taiwanese population. Issue 11 (15th November 2016) - Hung, Wei-Chieh; Wu, Jin-Shang; Sun, Zih-Jie; Lu, Feng-Hwa; Yang, Yi-Ching; Chang, Chih-Jen
Abstract : Objectives: Although metabolic syndrome correlates with erosive oesophagitis, few studies have examined the association between non-alcoholic fatty liver disease (NAFLD), associated with obesity and insulin resistance as metabolic syndrome, and erosive oesophagitis. The possible gender differences in risk factors of erosive oesophagitis should be considered. This study aimed to determine the concomitant effects of NAFLD and metabolic syndrome on erosive oesophagitis with respect to gender. Design, setting, participants and outcome measures: This cross-sectional study, conducted between January 2000 and August 2009, included 12 090 participants from the health examination center of a tertiary hospital. NAFLD was diagnosed according to ultrasonographic findings after excluding participants with excessive alcohol consumption or other liver diseases. Metabolic syndrome was determined using the revised National Cholesterol Education Program Adult Treatment Panel III criteria. Erosive oesophagitis was defined according to the Los Angeles classification by oesophagogastroduodenoscopy. Results: On the basis of the oesophagogastroduodenoscopic findings, the prevalence of erosive oesophagitis was 20.1% (n=1427/7110) and 9.9% (n=477/4842) in males and females, respectively. After adjusting for other variables, metabolic syndrome (OR 1.26; 95% CI 1.09 to 1.45) but not NAFLD (OR 1.14; 95% CI 0.98 to 1.30) significantly correlated with erosive oesophagitis in males, while NAFLD (OR 1.50; 95% CI 1.21 to 1.86) but not metabolic syndrome (OR 1.24; 95% CI 0.94 to 1.63) positively correlated with erosive oesophagitis in females. Conclusions: The detrimental effect on erosive oesophagitis is greater by metabolic syndrome than by NAFLD in males but greater by NAFLD than by metabolic syndrome in females.